ISLAM DAN DEMOKRASI: STUDI KOMPARATIF ANTARA TEORI POLITIK ISLAM DAN DEMOKRASI BARAT - Ihsan Nul Hakim (Jurnal Madania)
The relationship between democracy and Islam has been disputed materials among Muslim scholars. One of them said that democracy has similar understanding with the concept of Islamic politic, but the other one argued that both concepts about politics are different. The present article tries to describe the concept of Islamic politics and the relation to the democracy. The main question should be answered in this paper is whether the concept of democracy is equal to Islam or even in dispute. In one side, democracy as a governmental system is not in line with Islam because it does not mention clearly certain formulation of state. Otherwise, having humanity values, the democracy has similar concept to Islam because the values and the principles of politic gathered by democracy are not contradiction to the principles of Islamic politics.